The narrowing olfactory landscape of insect odorant receptors - Bohbot, Jonathan D.; Pitts, Ronald J. (Frontiers in Ecology and Evolution, 2015)
The molecular basis of odorant detection and its corollary, the task of the odorant receptor, are fundamental to understanding olfactory coding and sensory ecology. Based on their molecular receptive range, olfactory receptors have been classified as pheromone and non-pheromone receptors, which are respectively activated by a single pheromone component (“specialist”) or by multiple odorant ligands (“generalist”). This functional distinction is unique among ligand-gated ion channels and has shaped how we model olfactory coding both at the peripheral and central levels. Here, we revisit the longstanding combinatorial theory of olfaction and argue, based on physiological, pharmacological, evolutionary and experimental grounds that the task of the odorant receptor is not different from that of neurotransmitter receptors localized in neuronal synapses.